The Effects of Probiotic Supplementation on Functional Constipation Following Colonoscopy: A Double-blinded Randomized Controlled Trial - Soheilipour, Maryam; Khosravi, Leila; Tabesh, Elham; Jafari, Mohammad; Rabiee, Fatemeh; Tajabadi-Ebrahimi, Maryam; Adibi, Peyman (Current Nutrition & Food Science, 2025)
BackgroundFunctional constipation (FC) is characterized by infrequent and hard bowel movements, often accompanied by difficulty and pain during the passage. It has been suggested that an imbalanced microbiome contributes to the development of FC. One potential intervention is post-colonoscopy probiotic supplementation, which could create a favorable environment for FC patients.ObjectiveThis study aimed to investigate the effect of probiotic supplementation on relieving constipation in FC patients.MethodsThe current study was a double-blinded, randomized, placebo-controlled clinical trial (RCT) involving 78 patients with FC. Participants were randomly assigned to either the probiotic (n=39) or placebo groups (n=39). They received two capsules of either probiotic or placebo for 12 weeks. The assessment of bowel habit was based on ROME-IV criteria, which included anal obstruction feeling, defecation frequency, hard stool, painful defecation, force pushing, manual maneuvers, incomplete emptying, and total score. In addition, primary outcomes also included variables related to the Bristol Stool Form Scale (BSFS).ResultsProbiotic supplementation significantly decreased the ROME-IV total score and its other components, with the exception of defecation frequency, when compared to the placebo group (13.93± 0.57 vs. 17.77± 0.60; P<0.001). Furthermore, the risk of type I stool (RR: 0.036; 95% CI: 0.004-0.331) and II stool (RR: 0.076; 95% CI: 0.019-0.309) was significantly decreased in the probiotic group.ConclusionDespite some controversies surrounding the effects of probiotic supplementation on FC treatment, this RCT concluded that probiotic supplementation can improve bowel habits in FC patients.Clinical Trial Registration NumberClinical Trials (IRCT ID: IRCT20210817052219N1).
Keywords: ROME-IV